REGULATORY CONFLICT BETWEEN HALAL CERTIFICATION AND HOME FOOD INDUSTRY (P-IRT) LICENSE IN INDONESIA - Djakfar, Inayatillah; Kamri, Nor Azzah; Lubis, Asmuliadi (Online Journal of Islamic Management and Finance (OJIMF), 2025)
Recently, there has been a misalignment or overlap between regulations governing halal certification and the Home Industry Food Permit (P-IRT) in Indonesia. Products that have obtained distribution permits from the National Agency of Drug and Food Control (BPOM) or have PIRT certificates have been withdrawn by the Halal Task Force because they did not display the halal logo, even though they meet food safety standards. This study aims to analyze the main causes of regulatory issues between halal certification and the Home Industry Food Permit (P-IRT) in Indonesia, as well as provide effective recommendations for policy restructuring among the Ministry of Religious Affairs, the National Agency of Drug and Food Control (BPOM), the Health Office, and other relevant stakeholders. This study employs a qualitative approach by analyzing existing policies related to documents governing halal certification and P-IRT regulations, as well as its challenges and coordination among agencies. The findings indicate that the main cause of this issue is differences in interpretation, such as the varying definitions of the term "food product" and procedural interpretation. Furthermore, inadequate understanding of regulations arises from two standards that are not always aligned in technical requirements, such as hygiene requirements. Lastly, weak coordination between institutions is caused by the duality of supervision and certification, which are not integrated. These issues significantly impact business actors, especially Micro, Small and Medium Enterprises (MSMEs), who are often hindered in marketing their products. This study contributes to the development of a more harmonious policy framework between halal certification regulations and the Home Industry Food Permit (P-IRT). Furthermore, this study enriches the understanding of how halal product supervision, food safety and distribution permits can be implemented in a more integrated manner, in line with the principles of Islamic economics that support sustainability and the well-being of society. This study also recommends the need for procedure alignment, simplification or streamlining of procedures, and improved coordination between agencies through an integrated system. Thus, the synergy between halal certification and product distribution permits will not only strengthen national food security but also contribute to economic and social sustainability, increase public trust in local products, and support the management of Islamic wealth for a more sustainable future.